ANALISIS MENU ENGINEERING DALAM UPAYA MENINGKATKAN PENJUALAN MAKANAN DAN MINUMAN PADA MENU A'LA CARTE DI RESTORAN MALABAR COFFEE SHOP HOTEL HORISON BANDUNG - Sofyandi, Riyan Gusfaryanti (2015)
Sebuahrestoranmemegangperananpentingbagiperekonomianbisnis hotel.Untukiturestoranharusmampumeningkatkanpenjualan agar mendapatkankeuntungan yang maksimal.Sekaithal di halitu, menentukansuksesatautidaknyapenjualanpadasebuahrestoranperludilakukanpenelitianmenu engineeringuntukmengevaluasimenu yang tidak popular dantidakmenguntungkanbagirestoran.PenelitianinidilakukanpadaRestoran Malabar Coffee Shop Hotel Horison Bandung berkaitanpenerapankebijakanstandar food cost, penetapanhargajualdananalisismenu engineeringdalamupayameningkatkanpenjualan. Restoran Malabar Coffee Shop menetapkanstandar food cost 32%,lebihtinggidaristandar food cost 20-30%. Hal inimenarikbagipenelitiuntukmelakukananalisismenu engineering. Kata kunci: Standard Food Cost, PenetapanHargaJual, Menu Engineering A restaurant hold important role for the hospitality industry. Therefore, the restaurant must be able to increase sales in order to gain maximum benefit. Accordingly, a research to determine whether or not successful sales at a restaurant menu engineering needs to be done by evaluate the menu that are not popular and not profitable for the for the restaurant. This research was conducted at Malabar Coffee Shop Restaurant Hotel Horison Bandung related to the implementation of the standard food costs policy, the selling price determination, and analysis of menu engineering menu in an effort to improve sales. Restaurant Malabar Coffee Shops set the standard food cost 32 percent, higher than the standard 20-30 percent food cost. This was very interesting for menu engineering researchers to analyze. Key words: Standard Food Costs, Selling Price Determination, Menu Engineering